DIGITALIZATION AS A DRIVER OF CUSTOMER SERVICE PERFORMANCE: A CONCEPTUAL FRAMEWORK FOR CHINA’S AUTOMOTIVE LOGISTICS INDUSTRY - Li , Lu; Md Latip, Nor Azrin; Shokory, Suzyanty Mohd (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2026)
The accelerating pace of digital transformation has redefined how firms deliver value in logistics and service-oriented industries. This conceptual paper develops a framework that explains how digitalization functions as a strategic capability influencing customer service performance (CSP) within China’s automotive logistics sector. Grounded in the Resource-Based View (RBV), the paper conceptualizes digitalization as a valuable and inimitable resource that enhances organizational visibility, responsiveness, and reliability—key determinants of superior service outcomes. By integrating insights from logistics, information systems, and service management literature, the study positions digitalization as a direct enabler of customer satisfaction and loyalty, moving beyond traditional efficiency-based interpretations. The conceptual framework proposes that higher levels of digitalization lead to improved CSP through real-time data analytics, predictive service capabilities, and enhanced customer engagement. The discussion advances theoretical understanding of digital transformation as a source of service-based competitive advantage while providing practical guidance for managers seeking to leverage digital tools for service excellence. Policy implications are also outlined in relation to China’s Smart Logistics 2030 initiative. The paper concludes by suggesting future empirical research to validate the proposed framework and explore contextual moderators such as organizational agility and digital maturity.